Microbispora thailandensis sp. nov., an actinomycete isolated from cave soil - Duangmal K. (2017)
The taxonomic position of actinomycete strain NN276 T, isolated from cave soil, was studied using the polyphasic taxonomic approach. A phylogenetic tree based on 16S ribosomal RNA (rRNA) gene sequences showed that the isolate formed a distinct evolutionary linage with the genus Microbispora, with M. mesophila JCM 3151 T as its closest phylogenetic neighbor (97.9% similarity). The organism contained meso-diaminopimelic acid and the N-acetyl type of peptidoglycan. Madurose was detected in the whole-cell hydrolasate. The predominant menaquinones were MK-9(H 4), MK-9(H 2) and MK-9. Mycolic acids were not detected. Major phospholipids were diphosphatidylglycerol, hydroxy- phosphatidylethanolamine, phosphatidylethanolamine, phosphatidylinositol and phosphatidylinositol mannoside. The major cellular fatty acid was iso-C 16: 0 and GC content 70 mol%. DNA-DNA hybridization demonstrated that the isolate was distinct from M. mesophila JCM 3151 T. On the basis of phenotypic and genotypic data, it is proposed that strain NN276 T represents a novel species of the genus Microbispora, hence the name Microbispora thailandensis sp. nov. The type strain is strain NN276 T (BCC 41490 T NRRL B-24806 T NBRC 107569 T). © 2012 Japan Antibiotics Research Association All rights reserved.